Immune Evasion Strategies of Trypanosoma cruzi - Ana Flávia Nardy; Célio Geraldo Freire-de-Lima; Alexandre Morrot (Journal of Immunology Research)
Microbes have evolved a diverse range of strategies to subvert the host immune system. The protozoan parasite Trypanosoma cruzi, the causative agent of Chagas disease, provides a good example of such adaptations. This parasite targets a broad spectrum of host tissues including both peripheral and central lymphoid tissues. Rapid colonization of the host gives rise to a systemic acute response which the parasite must overcome. The parasite in fact undermines both innate and adaptive immunity. It interferes with the antigen presenting function of dendritic cells via an action on host sialic acid-binding Ig-like lectin receptors. These receptors also induce suppression of CD4+ T cells responses, and we presented evidence that the sialylation of parasite-derived mucins is required for the inhibitory effects on CD4 T cells. In this review we highlight the major mechanisms used by Trypanosoma cruzi to overcome host immunity and discuss the role of parasite colonization of the central thymic lymphoid tissue in chronic disease.